2021
DOI: 10.3390/en14113182
|View full text |Cite
|
Sign up to set email alerts
|

Factors for Bioeconomy Development in EU Countries with Different Overall Levels of Economic Development

Abstract: The aim of this article is to indicate the rationale for the development of the bioeconomy in selected EU countries depending on their overall level of economic development. The research was based on four highly developed countries, i.e., Germany, France, Finland and Denmark, and four medium-developed countries, i.e., Poland, Hungary, Czech Republic, and Slovakia for the period 2001–2018. Renewable energy consumption, biomass and agricultural production were analysed as determinants of the bioeconomy developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…A balance must therefore be found between ensuring food security for society and protecting the environment. Thus, Agriculture supplies key resources that the bioeconomy can use (Czyżewski et al, 2021). The percentage of workers in the Bio-based textiles sector also decreased (by 0.8 pp.).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A balance must therefore be found between ensuring food security for society and protecting the environment. Thus, Agriculture supplies key resources that the bioeconomy can use (Czyżewski et al, 2021). The percentage of workers in the Bio-based textiles sector also decreased (by 0.8 pp.).…”
Section: Resultsmentioning
confidence: 99%
“…The bioeconomy concept is a response to the problems and challenges of today's world (Czyżewski, Grzyb, Matuszczak & Michałowska, 2021). Although a lot of damage due to irresponsible management cannot be reversed, the contemporary generation is responsible for redesigning the management into a different paradigm and reformulating the management objectives, and -most importantly -implementing methods of production that will not generate external effects (Pink & Wojnarowska, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, the authors concluded in a trenchant manner that “bioeconomy literature is making hardly any contribution to the debates and social currents that link gender, development, and sustainability” where “women are simply named”. Thirdly, by encompassing the quality of informal institutions in our analysis, we seek to emphasize how these unofficial norms are connected to the evolution of the bioeconomy (see also [ 24 ]). We believe that aggregating a world with the attributes of sustainability cannot be conceived outside the existence of good practices.…”
Section: Introductionmentioning
confidence: 99%
“…The article by Czy żewski et al [3] concerned the premises of bio-economy development in selected EU countries depending on their general level of economic development. The research compared highly developed countries (Germany, France, Finland, and Denmark) and four countries with a relatively lower level of development (Poland, Hungary, the Czech Republic, and Slovakia).…”
mentioning
confidence: 99%